Pembuktian dan Penjatuhan Putusan Pidana Terhadap Terdakwa Tindak Pidana Penganiayaan (Studi Kasus Putusan Nomor 26/Pid.B/2016/Pn.Tab.) - I Putu Hendra Setyawan; I Made Arjaya; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—Crime is an act or series of acts that can be subject to criminal law. One form of crime is persecution. Persecution is a form of harming or torturing people or intentionally reducing and damaging the health of others. The main problem is how the application of sanctions for criminal acts of abuse by public prosecutors and how the judges consider in the case of criminal acts of abuse. The research method used in writing this thesis is a type of normative legal research. Whereas the approach uses the conceptual approach, the legal approach and the case approach. The application of criminal sanctions for maltreatment by public prosecutors refers to article 351 paragraphs (1) of the Criminal Code which has been adjusted to article 3 of the Supreme Court Regulation of the Republic of Indonesia No.2 of 2012 concerning adjustments to the limits of minor criminal offenses and the amount of fines in KHUP. Whereas the judge considers each indictment from the public prosecutor, the defendant has fulfilled a single indictment and is based on the process of examining evidence, namely testimony of witnesses, letters, statements of the defendant, instructions, and evidence. In the trial the facts that ordinary crimes had been committed were proven. Thus the Panel of Judges ruled with a sentence of 4 (four) months imprisonment.